Supervisor Support and Job Satisfaction: Systematic Literature Review (SLR) - Fuad Alfaridzi Setiawan; Sopiah Sopiah (Journal of Creative Student Research, 2023)
Background: Supervisor support behavior in a way that optimizes the use of employee knowledge, skills and attitudes acquired in on-the-job training. By getting positive support from the leadership and all employees, employee work performance will be motivated to be better. Objective: This article presents a systematic literature review of supervisor support and job satisfication. Method: Descriptive research with a qualitative approach, systematic literature review study. Researchgate, Google Scholar and ScienceDirect searches reviewed supervisor support and job satisfication. A total of 13 studies conducted between 2014-2023 were included in this review. Results: A total of 141.700 titles were identified and found 13 studies that met the requirements/criteria which discussed supervisor support and job satisfication. Conclusions: Positive support from the leadership and all employees will encourage employee work performance to be better. Apart from that, support also provides encouragement to employees so that they can trust and help each other, as well as good relations between employees in the work environment.